Catalytic synthesis of SiC nanowires in an open system. Issue 6 (22nd January 2019) - Kao, Kechen; Jiang, Min; Ding, Lijuan; Lin, Wenxin; Chen, Jianjun
Abstract: SiC nanowires (NWs) are usually synthesized in a closed vacuum reaction system which limits the yield of SiC NWs. In this work, SiC NWs and carbon nanotubes were synthesized in an open tube furnace at 1550°C with Si powder as silicon sources, ethanol as carbon sources and ferrocene as catalyst. The as‐synthesized products were ultralong β‐SiC NWs with the diameter about 80‐100 nm and the length up to several tens micrometers. The diameter of the carbon nanotubes was about 20‐30 nm. The carbon nanotube yarns about 20 cm in length were obtained at the end of the tube furnace. The growth mechanism of SiC NWs and carbon nanotubes were proposed. Compared with the traditional synthetic techniques in the high vacuum closed system, the novel synthesis method in the open system provided a new approach to the synthesis of SiC NWs.